Fuel Economy Improvement Analysis of Parallel and Power-Split Hybrid Electric Vehicles - Kang, Hye Hyun; Chung, In Chun; An, Kwang Man; Park, Jin Il; Lee, Jong Hwa (International Journal of Automotive Technology, 2022)
The demand for the development of low-emission vehicles is increasing aided by a global trend toward gradual enforcement of regulations on fuel economy and emissions of vehicles. The market share of HEVs is expected to grow from 5 % in 2015 to 17.5 % in 2050. The purpose of this study is to quantitatively evaluate the strengths and weaknesses of parallel HEV and power-spilt HEV for each powertrain system element. Power-split HEV has a drawback of power circulation, and for this reason, more energy has been generated by engine. Engine operational time and the engine loss of the power-split HEV are greater than that of parallel HEV. The advantage of power-split HEV is that it has a simple structured drivetrain compared to parallel HEV. Therefore, the drivetrain loss is less. Accordingly, the fuel consumption of the parallel HEV and power-split HEV is about the same in the UDDS 2 cycle, 17.1 % less in parallel HEV in HWFET. In HWFET, the disadvantage of the power-split HEV is more influential, and it appears that the fuel economy is worse than that of the parallel HEV.
Keywords: Electric power; Energy flow; Energy flow down; HWFET; Hybrid electric vehicle; Parallel hybrid electric vehicles; Power split hybrid electric vehicles; UDDS; Vehicle energy; Vehicle energy management; Energy flow down; Fuel economy; HWFET; Hybrid electric vehicle (HEV); UDDS; Vehicle energy management